2021
DOI: 10.1093/cdn/nzaa110
|View full text |Cite
|
Sign up to set email alerts
|

Use of Text Messaging and Facebook Groups to Support the Healthy Children, Strong Families 2 Healthy Lifestyle Intervention for American Indian Families

Abstract: Background Few obesity interventions have been developed for American Indian (AI) families despite the disproportionate risk for obesity experienced within AI communities. The emergence of mobile technologies to enhance intervention delivery may particularly benefit AI communities, many of which are hard-to-reach and underserved. Objective This study aimed to assess the use and perceptions of text messaging and Facebook to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…After full‐text screening, an additional 37 studies were identified. These included 20 studies 5,70–88 reporting 12 additional interventions and 17 studies 89–105 reporting outcomes from the interventions included in the review by Karacabeyli et al but those published after July 2017. The search of the clinical trial registries, the gray literature, and reference lists of included studies identified an additional 32 studies for inclusion in our review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text screening, an additional 37 studies were identified. These included 20 studies 5,70–88 reporting 12 additional interventions and 17 studies 89–105 reporting outcomes from the interventions included in the review by Karacabeyli et al but those published after July 2017. The search of the clinical trial registries, the gray literature, and reference lists of included studies identified an additional 32 studies for inclusion in our review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…As for tourism, this sphere is certainly one of the most effective, capable of contributing to the development of children's and adolescents' skills and attraction to a healthy lifestyle. In addition, tourism allows developing the imagination of the younger generation about ways to spend useful leisure, as well as active and sports recreation associated with cold training of the body or relieving fatigue (Tomayko et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Individual and community-level factors that likely influence engagement include phone ownership, network access, cost of devices, network infrastructure, and location [ 34 ]. One SMS intervention to support healthy lifestyle interventions among AI families reported different engagement levels based on urban and rural status, where urban participants liked and commented on posts more than rural participants [ 35 ] Phone number changes may also account for lower engagement. The Healthy Children, Strong Families 2 study reported that nearly one-third of AI participants changed their phone number during the intervention [ 35 ].…”
Section: Discussionmentioning
confidence: 99%